La informática y su relación con el rendimiento académico de los niños/as de 5 años de las I.E inicial de la ciudad de Rioja - Vásquez Barturén, Yothy Ruth (2011)
The present investigation aims to determine the correlation between computar science and the academic achievement of the currículum areas of personal-social, communication, mathematics and science and environment of children aged 5 years of early childhood educational institutions of the city Rioja. The study is important because it allows to describe the presence of information of chi'ldren in different settings: home, school and internet booths for the development of their capabilities. The main objective of this study was to describe the relationship between computar science and the academic performance of children 5 years of initial education and the specific objectives were to describe the academic performance of children of 5 years, describing computing children from 5 years to establish the relationship between academic performance computing for children 5 years and infer the results of the relationship between academic performance computing for children 5 years the early childhood educational institutions of the city of La Rioja. The computer is based on theories of artificial intelligence, cognitiva, sociocultural and constructivist, who claim that computing is an important teaching tool for the deve'lopment of the learning sessions. The theory allows us to pose the following hypothesis: There is a relationship between academic performance computing for children 5 years of early childhood educational institutions of the city of La Rioja, 2011 Methodologically, the research design was descriptiva and correlational with a sample of 120 children in the educational institutions of the city of La Rioja, and in the process of statistical analysis it was found that the central hypothesis is accepted or research with a confidence 95%, and the value that is obtained from the Pearson correlation coefficient to be a weak positiva correlation that is explained by the 1. 12% of the population.